Optimalisasi Pemanfaatan E-Commerce dan Media Sosial dalam Transformasi Bisnis UMKM Tradisional di Desa Sumur Batu - Yoyok Priyo Hutomo; Rachmat gunawan; Chandra Ayu Pramestidewi; Muhamad Rizki Ramdani; Siti Sonia; Wita Sri Rahayu; Hamdun Hamdun; Muhamad Azmi (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The development of digital technology has presented new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to enhance their competitiveness and business sustainability. However, traditional MSMEs in Sumur Batu Village still face limitations in product branding and the effective utilization of e-commerce and social media for marketing and business transformation. Through this Community Service Program (PKM), students and local communities have collaborated to provide solutions grounded in humanitarian values, by empowering MSME actors through mentorship, training, and applicable knowledge transfer. This effort not only focuses on the technological aspect but also builds self-confidence, independence, and solidarity among business owners and the village community. The results of the activity show an increase in the digital understanding and skills of the MSME actors, which is expected to drive local economic sustainability while strengthening social bonds. Thus, optimizing the use of e-commerce and social media is not merely a business transformation, but also a humanitarian movement to create shared prosperity.